Detection of Selenium and Nickel Metal Ion in Water Using Mn3O4-Cn-Modified Electrode - Neetha John; K. E. Abraham (International Journal of Electrochemistry)
The present study reports the design of the Mn3O4-Cn electrode and its use for simultaneous detection of selenium and nickel in water. The designed electrode can be used as a convenient electrochemical device for on-site testing of Se (IV) and Ni (II) levels in affected regions. The best responses are obtained with 0.1 M phosphate buffer saline (PBS) and 5 mM Fe (CN)6 as supporting electrolyte. The scan rate and the number of cyclic repetitions have a great effect on peak shape and intensity. It is seen from our study that peak intensity is directly proportional to Se (IV) and Ni (II) concentrations in the range of 5 to 250 µg/L (correlation coefficients 0.952 and 0.984) when the optimized parameters are used. The detection limit of 0.533 µg/L Se (IV) and 0.718 µg/L for Ni (VI) with a response time of 18 s for 5–250 µg/L concentration is obtained, respectively. Enhanced analytical results for different water samples establish that the proposed method is appropriate for Se (IV) and Ni (II) detection. FESEM images confirm the Mn3O4-Cn nanocomposite formation on the electrode.